Bioinformatic Analysis of Gene Expression Profile in Plasma of Hypertensive Patients - Li, Yan-zhen; Xu, Hao-jie; Hu, Jia-min; Lin, Shi-zhu; Zhang, Na; Cai, Hong-da; Zeng, Kai; Liang, Min; Lin, Zhi-jian; Lin, Cai-zhu; Wu, Xiao-dan (American journal of hypertension, 2020)
Abstract Background To analyze expression profiles of long noncoding RNA (lncRNA) and messenger RNA (mRNA) in patients with essential hypertension (EH) and normotensive adults. Methods The gene chip dataset GSE76845, which was generated from 5 plasma samples from patients with EH and 5 normotensives, was downloaded from the National Biotechnology Information Center Public Data Platform. Each sample (total RNA) was pooled from the total RNA of 3 age- and gender-matched subjects (EH patients or healthy controls). A ClusterProfiler package including gene set enrichment analysis (GSEA) was used to identify differentially expressed genes. The target microRNA and mRNA were predicted by microcode, microDB, microTarBase, and TargetScan databases. Finally, a competing endogenous RNAs (ceRNA) regulatory network was constructed. Results Compared with the healthy control adults, 191 differential lncRNAs (90 upregulated and 101 downregulated) and 1,187 differential mRNAs (533 upregulated and 654 downregulated) were identified in EH patients. GSEA analysis showed that 17 pathways, including ubiquinone and terpenoid-quinone biosynthesis, parathyroid hormone synthesis secretion and action, fatty acid metabolism, and steroid hormone biosynthesis are involved in hypertension. A ceRNA network consisting of 150 nodes and 488 interactive pairs was constructed. Conclusions lncRNA and mRNA profile analysis provides new insight into molecular mechanisms of EH pathogenesis and potential targets for therapeutic interventions.